Pemberdayaan Masyarakat melalui Diversifikasi Tanaman Hortikultura sebagai Upaya Peningkatan Ketersediaan Pangan dan Gizi Keluarga - Yusnaini, Yusnaini; Dina Andriani Br Karo; Jaka Syahputra; Nandara Priyanti Elna (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Desa Rumah Kampung, located in Lawe Alas District, Southeast Aceh, primarily produces rice and corn. The community uses most of the rice for basic needs and livestock feed, with the remainder sold as a source of income. However, 45% of agricultural output does not meet food needs, 60% of the community still buys cooking ingredients, and there is limited access to agricultural products, a lack of food diversification, and 40% of the community does not cultivate horticultural crops. This Community Service Program (PKM) aims to increase understanding of the significance of horticultural crop diversification in supporting food security and family nutrition. The PKM implements the participatory rural appraisal method, including socialization, training, land preparation, seed procurement, planting, and horticultural crop maintenance. A total of 25 participants (20 housewives and 5 youth) were involved in the activity. The results of this program include a rise in the community's knowledge of horticultural crop cultivation, with the mean score before the exam being of 55.8 and the mean score after the test being 66.2, improved horticultural skills, active community participation in seed procurement and planting, and enhanced horticultural crop diversification. This community empowerment activity contributes to the increased availability of diverse food and improved family nutrition.